Postoperative adjuvant immunotherapy and molecular targeted therapy for patients of hepatocellular carcinoma with portal vein tumor thrombus after hepatectomy: a propensity score matching study - Zhou, Jiangmin; Xiong, Huifang; Zhang, Zhiwei; Chen, Dong; Wang, Wei; Zhou, Cheng; Wu, Biao (Frontiers in Surgery, 2024)
Portal vein tumor thrombus (PVTT) is a major risk factor of recurrence of hepatocellular carcinoma (HCC) after hepatectomy. Whether postoperative adjuvant immunotherapy and molecular targeted therapy (I-O and MTT) is effective in reducing the risk of recurrence of HCC with minimal portal invasion after hepatectomy and improving prognosis is unknown. We collected the data of HCC with Vp1 or Vp2 PVTT patients who underwent hepatectomy at our center between January 2019 to June 2022 from the hospital database. We utilized propensity score matching (PSM) to establish a 1:1 match between the postoperative group treated with I-O and MTT and the postoperative group without I-O and MTT. To compare the recurrence-free survival (RFS) and overall survival (OS) between the two groups, we employed the Kaplan-Meier method. Additionally, we conducted Cox regression analysis to identify the prognostic factors that influence patient prognosis. To account for different high-risk factors, subgroup analyses were carried out. Among the 189 patients included in the study, 42 patients received postoperative adjuvant I-O and MTT. After PSM, the 1, 2years RFS were59.2%, 21.3% respectively in the I-O and MTT group and 40.8%, 9.6% respectively in the non-I-O and MTT group. The median RFS was 13.2 months for the I-O and MTT group better than 7.0 months for the non-I-O and MTT group (P = 0.028). 1, 2-years OS were 89.8%, 65.8% respectively in the I-O and MTT group and 42.4%, 27.7% respectively in the non-I-O and MTT group. The median OS was 23.5 months for the I-O and MTT group better than 17.2 months for the non-I-O and MTT group (P=0.027). Multivariate analysis showed that postoperative adjuvant I-O and MTT was a prognostic protective factor associated with OS and RFS. The most frequent AE observed in this study was pruritus, and rare AEs included decreased platelet, hypothyroidism, proteinuria, myocarditis and hypoadrenocorticism. The incidence of GRADE ≥3 AE with no deaths recorded. The study suggested that postoperative adjuvant I-O and MTT strategy was beneficial to improve the prognosis of HCC patients with PVTT patients, while the therapy was safe and reliable.